Molecular typing of Candida albicans strains isolated from nosocomial candidemia - Branchini, Maria Luiza Moretti; Geiger, Débora de Cassia Pires; Fischman, Olga; Pignatari, Antonio Carlos (Revista do Instituto de Medicina Tropical de São Paulo, 1995)
Yeasts of the genus Candida have been recognized as important microorganisms responsible for nosocomial fungemia. Six blood-stream and two intravenous central catheter C. albicans strains were isolated from eight patients and studied by electrophoretic karyotyping of chromosomal DNA by pulsed-field gel electrophoresis. Seven chromosomal DNA profiles were identified. Two patients showed isolates with the same profile, suggesting nosocomial transmission. Karyotyping of C. albicans revealed an excellent discriminatory power among the isolates and may therefore be useful in the study of nosocomial candidemia.